2019
DOI: 10.4491/eer.2019.174
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical degradation of Orange G in K<sub>2</sub>SO<sub>4</sub> and KCl medium

Abstract: In this work, a detailed study on the electrochemical degradation of an azo dye, Orange G is performed using a platinum electrode. Indeed, the influence of the dye concentration (50-150 mg/L), the pH of the medium and the density of the electric current is studied on the rate of discoloration, the rate of mineralization, the efficiency of the electric current and the energy consumption. The UV-visible spectra of OG plotted against the degradation time show the decrease of the intensity of the characteristic dy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…In contrast, in the study of Silva et al, which showed the first-order removal of TOC, EE/M exhibited far greater variations with time (31–37%) than EE/O (6–11%) . However, by high current operations for utilizing the oxidant generation reaction, pollutant removal generally follows first-order kinetics in most EOPs, where the use of EE/O is practically appropriate. More details about the dependences of EE/O and EE/M on the operating parameters (including initial organic load and j ) are provided in the subsequent sections.…”
Section: Performance Evaluation Of Eopsmentioning
confidence: 99%
“…In contrast, in the study of Silva et al, which showed the first-order removal of TOC, EE/M exhibited far greater variations with time (31–37%) than EE/O (6–11%) . However, by high current operations for utilizing the oxidant generation reaction, pollutant removal generally follows first-order kinetics in most EOPs, where the use of EE/O is practically appropriate. More details about the dependences of EE/O and EE/M on the operating parameters (including initial organic load and j ) are provided in the subsequent sections.…”
Section: Performance Evaluation Of Eopsmentioning
confidence: 99%
“…Its high chemical resistance to corrosion as well as its stability in very aggressive environments have favored its use in the electrochemical degradation of pollutants [28]. Hamous et al [29] reported the anodic oxidation of Orange G (75 mg.L −1 ) azo dye using platinum electrode. After 240 minutes of electrolysis, maximum color removal efficiency of 68.35% in K2SO4 (0.1 M) and 100% in KCl (0.1 M) were obtained at 50 mA.cm −2 current density.…”
Section: Platinummentioning
confidence: 99%
“…Their data showed that carbon fiber had higher activity than graphite and the removal efficiency is proportional to the applied current . The selection of the proper electrolyte solution is also a significant factor in the electrochemical reactions . The wastewater has various ions, such as Cl – , CO 3 2– , and HCO 3 – , that can rapidly interact with the produced OH • , inhibiting pollutant destruction .…”
Section: Introductionmentioning
confidence: 99%